2009
DOI: 10.1152/jn.01138.2007
|View full text |Cite
|
Sign up to set email alerts
|

Learning of a Sequential Motor Skill Comprises Explicit and Implicit Components That Consolidate Differently

Abstract: The ability to perform accurate sequential movements is essential to normal motor function. Learning a sequential motor behavior is comprised of two basic components: explicit identification of the order in which the sequence elements should be performed and implicit acquisition of spatial accuracy for each element. Here we investigated the time course of learning of these components for a first sequence (SEQA) and their susceptibility to interference from learning a second sequence (SEQB). We assessed explici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 29 publications
8
87
0
4
Order By: Relevance
“…Therefore, we propose that functionally distinct subpopulations of neurons within M1 encode and express different parameters of motor sequence learning, with one population tuned to the more rapidly learned, explicit, stimulus-response component of the task and the other tuned to the more slowly learned, procedural, sensorimotor integration component of the task. This is consistent with results from our laboratory (Savion-Lemieux et al, 2009) and others (Grafton et al, 2008;Ghilardi et al, 2009) that, together, describe a spectrum of parameters that can be differentially optimized over the course of learning. Although M1 activity during early learning was found to correlate with the behavioral consequences of consolidation on this sequence learning task, the brain areas that actually participate in consolidation cannot be directly addressed with this experiment.…”
Section: M1 As a Predictor Of Consolidationsupporting
confidence: 91%
“…Therefore, we propose that functionally distinct subpopulations of neurons within M1 encode and express different parameters of motor sequence learning, with one population tuned to the more rapidly learned, explicit, stimulus-response component of the task and the other tuned to the more slowly learned, procedural, sensorimotor integration component of the task. This is consistent with results from our laboratory (Savion-Lemieux et al, 2009) and others (Grafton et al, 2008;Ghilardi et al, 2009) that, together, describe a spectrum of parameters that can be differentially optimized over the course of learning. Although M1 activity during early learning was found to correlate with the behavioral consequences of consolidation on this sequence learning task, the brain areas that actually participate in consolidation cannot be directly addressed with this experiment.…”
Section: M1 As a Predictor Of Consolidationsupporting
confidence: 91%
“…This may be particularly important for a technique like tDCS (which may exert its effect through the alteration of thresholds for neuronal discharge (Fritsch et al, 2010)) as observed effects may be highly dependent on the specific context in which it is applied. Currently, the most frequently used tasks to investigate motor skill learning in experimental settings are: (1) sequential finger tapping tasks (SFTT; which can include either implicit or explicit sequence structure) (Ghilardi, Moisello, Silvestri, Ghez, & Krakauer, 2009;Nitsche et al, 2010;Reis et al, 2015;Song & Cohen, 2014); and (2) the sequential visual isometric pinch force task (SVIPT) (Reis et al, 2009). In a sense, these tasks are complimentary in that for the SFTT, the main unit of action is rather trivial for a healthy subject to accomplish (i.e.…”
Section: Motor Learningmentioning
confidence: 99%
“…During this interval, there is no further practice, or even mention, of the procedure, and learning remains largely tacit or implicit (Brown & Robertson, 2007;Hallgato, Gyori-Dani, Pekar, Janacsek, & Nemeth, 2013;Krakauer & Shadmehr, 2006;NĂ©meth et al, 2010). Consolidation is also sometimes referred to as resistance to interference and forgetting (Ghilardi, Moisello, Silvestri, Ghez, & Krakauer, 2009;Goedert & Willingham, 2002; Stephan, Meier, Orosz, Cattapan-Ludewig, & KaelinLang, 2009). In the present study, we use the first definition (i.e., further improvement or enhancement).…”
Section: Introductionmentioning
confidence: 99%
“…wakefulness and time of day (Brawn, Fenn, Nusbaum, & Margoliash, 2010;Cajochen et al, 2004;Della-Maggiore, 2005;Doyon et al, 2009;Fischer, Hallschmid, Elsner, & Born, 2002;Keisler, Ashe, & Willingham, 2007;Kuriyama, Stickgold, & Walker, 2004;Manoach et al, 2004;Maquet, Schwartz, Passingham, & Frith, 2003;Peigneux et al, OFFLINE CONSOLIDATION 4 2003;Spencer, Sunm, & Ivry, 2006), and degree of explicit awareness (Ghilardi et al, 2009;Hotermans, Peigneux, Maertens de Noordhout, Moonen, & Maquet, 2006;Robertson, Pascual-Leone, & Press, 2004). It is not yet clear how sequence learning per se changes from a labile state to a more stable one, although there is a large body of work on motor memory consolidation (see Krakauer & Shadmehr, 2006, for a review).…”
Section: Introductionmentioning
confidence: 99%